Cover Picture: Plasma Process. Polym. 7/2018. Issue 7 (19th July 2018) - Almansoori, Alaa; Masters, Robert; Abrams, Kerry; Schäfer, Jan; Gerling, Torsten; Majewski, Candice; Rodenburg, Cornelia
Abstract : Front Cover: Low pressure plasma treatment and atmospheric pressure plasma jets were applied for the surface modification of Polyamide 12 powder (PA12, bottom) used in Laser Sintering. Different treatment times (middle) and plasma sources (kINPen ® IND, top; Hairline, and Zepto) were used. Low pressure plasma treated PA12 showed an increase in wettability, powder porosity, and possessed a higher density resulting in poor melting behavior for treatment times of up to 3h. Brief atmospheric pressure plasma (several minutes) treatments demonstrated similar changes in contouring and deepening of morphological features as observed by low voltage scanning electron microscopy, but crucially, the short atmospheric pressure plasma treatment with Hairline retained the favorable melt characteristics of PA12 powder. Further details can be found in the article by Alaa Almansoori et al. (e1800032 ).